Exploring Biomass Waste-Derived Biochar as a Catalyst for Levulinic Acid Conversion to γ-Valerolactone: Insights into Synthesis, Characterization, and Catalytic Performance - Joao Carlos Alves Macedo; Maryam Shirinkar; Richard Landers; André Henrique Rosa (Biomass)
The transition from fossil resources to renewable raw materials derived from lignocellulosic waste is crucial for economic and environmental sustainability. Advancing toward a bio-based economy necessitates the development of innovative heterogeneous catalysts. This study explores the use of modified sugarcane bagasse biochar, embedded with ruthenium and iron particles, as a green catalyst for converting levulinic acid (LA) to γ-valerolactone (GVL). The efficiency of both raw and modified biochar in the LA to GVL conversion process, utilizing formic acid (FA) exclusively as the hydrogen source, was systematically assessed through characterization techniques, including XRD, TGA, XPS, and SEM/EDS. The gelification method using alginate enhanced the ruthenium and iron content on the surface of the biochar. The results demonstrate that the modified material has significant potential for efficient LA-to-GVL conversion, achieving a yield of 73.0 ± 9.2% under optimized conditions (0.5 g of BC500Fe/3%Ru at 180 °C for 3 h, with 4 mmol LA, 8 mmol FA, and 10 mL of water). Iron on the biochar surface facilitated the formation of adsorption sites for LA, supporting the notion of this novel catalyst for LA conversion in an aqueous medium in the presence of FA. This research underscores the potential of this green catalyst in advancing sustainable biomass conversion and contributes to the ongoing shift towards a bio-based economy.